PROFILE OF METABOLIC SYNDROME COMPONENTS IN OBESE ADOLESCENTS: STUNTING VS. NON-STUNTING - Harits, Muhammad; Widjaja, Nur Aisiyah; Ardiana, Meity (The Indonesian Journal of Public Health, 2024)
Introduction: Stunted children are more likely to become obese, with a prevalence of 1.33% in children under the age of five. Aims: To evaluate the metabolic syndrome (MetS) profile in overweight/obese adolescents who are either stunted or not, and to determine the associations between stunting characteristics (height-for-age z-score, or HAZ) and anthropometric measurements (waist circumference, hip circumference, and waist-to-hip ratio), as well as MetS indicators. Methods: A retrospective observational study was conducted focusing on adolescents who were overweight or obese. Subjects were divided into 2 groups based on height-for-age z-score (HAZ): stunting group and non-stunting group. Subject numbers were determined by total sampling due to the number of stunted being small. Results: The prevalence of MetS in stunting overweight/ obese adolescents was 18.75%, dominated by female. There was a significant difference on BMI (34.60 (26.80-45.09) vs. 31.11 (27.34-40.13, p=0.040), waist-to-height ratio (0.63 (0.54-0.73) vs. 0.58 (0.52-0.64), p=0.005), hip circumference (111.27 (95-135) vs. 102.50 (87-114) cm, p=0.012) and systole blood pressure (124.37 (110-140) vs. 116.25 (100-130) mmHg, p=0.032), greater in stunting subjects than non-stunting. Waist-to-hip ratio was lower in stunting than non-stunting (0.85 (0.69-0.97) vs. 0.92 (0.81-0.99), p=0.012). HAZ was correlated negatively with BMI (r=-0.358, p=0.044), but correlated positively with hip circumference (r=0.215, p=0.023). Conclusion: Adolescents who were stunted and overweight/obese exhibited higher values for BMI, waist-to-height ratio, hip circumference, and systolic blood pressure compared to non-stunted individuals who were overweight/obese. There was a correlation between the height-for-age z-score and both BMI and waist-to-hip ratio.